Ethical leadership : creating and sustaining an ethical business culture - Leigh, Andrew (London : Kogan Page, 2013)
" The demand from society for organizations to be ethical and responsible is growing, and the cost of irresponsible behavior is often huge. Unethical action can dramatically affect the future of a company or destroy it all together.Ethical Leadership shines a light on the role of both culture and ethics in organizations by making the issues more transparent, accessible and above all, connected. Business leaders are now accountable for showing that they have the correct ethical policies and culture in place. Cultural and behavioral change consultant Andrew Leigh focuses on the fact that ethical culture is manifest in the actual behavior and attitudes of all staff, rather than in policy documents.While there are very few absolutes when it comes to ethics, there are clear ways to be a responsible leader, and Ethical Leadership is full of practical strategies, case studies and action points which will help leaders to improve and manage ethical culture in their organizations"--
"Ethical Leadership shines a light on the role of both culture and ethics in organizations by making the issues more transparent, accessible and above all, connected. Business leaders are now accountable for showing that they have the correct ethical policies and culture in place. Andrew Leigh focuses on the fact that ethical culture is manifest in the actual behaviour and attitudes of all staff, rather than in policy documents. His book is full of practical strategies, case studies and action points which will help leaders to improve and manage ethical culture and climate in their organizations"--
Machine generated contents note: -- IntroducionPart One Making sense of ethical leadership01 Making sense of culture -- What is culture? -- Culture shifts -- Avoiding the rocks -- Assessing your culture02 The ethical advantage: what's in it for your organization? -- Some specific benefits of an ethical culture -- Recognizing an ethical company -- Staying clear of trouble: avoiding risk -- Why values matter -- Making sense of ethics03 Towards an ethical culture -- Myths that can undermine the culture -- Moving beyond the myths -- Building a strong ethical foundation -- Where do we start building? -- A systems approach -- A step-by-step approach -- EntropyPart Two Organizational requirements04 Driving forces for an ethical culture -- External drivers -- Expect resistance -- Internal drivers -- Values driven -- Employee expectations -- Wholehearted engagement -- A new driver05 Leadership and management of ethical cultures -- Trust -- Authenticity -- Tone -- Engagement -- General engagement -- Ethical engagement06 Systems and procedures -- Policies -- Codes and rules -- Metrics -- Decisions rules -- Business processes -- Reporting structures -- Danfoss -- reporting structure07 Communication strategy -- A continuous free flow of communications -- A targeted approach -- Alignment -- Trust in managers and leaders -- Accountability -- Enlivening communication -- Persistent monitoring -- Make it an obsession08 Champions and exemplars -- Role models -- Leadership on the line -- Part Three Individual requirements09 Learning: will and skill -- Will -- Skill -- Developing people's skills -- Is training cost-effective? -- Can't it all be done online? -- Leaders need help too10 Learning: rehearse -- Creating ethical conduct -- Is this ethical? -- Rehearsing for real -- Behavioural simulation -- Action planning and action learning11 Sustaining: support -- Raise awareness -- Sharpen sensitivity -- Grow confidence -- Build courage -- Conclusion12 Sustaining: rewards -- Building the reward strategy -- Trigger 1: Identify -- Trigger 2: Review -- Trigger 3: Communicate -- Trigger 4: Train -- Trigger 5: Collect -- Trigger 6: Monitor -- Trigger 7: Evaluate and refinePart Four Sustaining the shift13 Over the horizon: the future of ethical leadership -- Globalization -- Society shifts (societal changes) -- Demographic shifts -- Technological advance -- Requirements for a low-carbon economy -- Over the horizon -- Summing up -- Resources -- The Ethical Leadership Litmus Test -- Index.
Includes bibliographical references and index.
Keywords: Business ethics; Corporate culture